2016
DOI: 10.5301/jabfm.5000325
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Graphene Oxide on Bacteria and Peripheral Blood Mononuclear Cells

Abstract: Our experiments provide vital information for future applications of GO in suspension. If its antibacterial properties are to be potentiated, care should be taken to select 2D sizes in the micrometer range, and exposure should not be carried out in the presence of grow media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…However, the exposure of bacteria to GO was carried out in the presence of growth medium, which has proven to saturate the basal planes of graphene and suppress any effect it could have. 7 In a previous contribution by our group, 10 we performed a systematic study of the antibacterial effect of GO on E. coli by monitoring the dynamic growth measuring the OD (optical density) of bacterial suspensions; the interaction of the material with bacteria was carried out in saline solution for 1 h, observing concentration- and size-dependent effects, agreeing with the results of other reports under the same experimental conditions. 8,12,13 …”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, the exposure of bacteria to GO was carried out in the presence of growth medium, which has proven to saturate the basal planes of graphene and suppress any effect it could have. 7 In a previous contribution by our group, 10 we performed a systematic study of the antibacterial effect of GO on E. coli by monitoring the dynamic growth measuring the OD (optical density) of bacterial suspensions; the interaction of the material with bacteria was carried out in saline solution for 1 h, observing concentration- and size-dependent effects, agreeing with the results of other reports under the same experimental conditions. 8,12,13 …”
Section: Introductionsupporting
confidence: 81%
“…In this study, our characterization and previous works account for the purity of GO; 10,23 the flakes used show lateral dimensions of 100 nm according to previous reports. 10 Regarding the exposure methodology, we have chosen to carry out the first contact of our materials with bacteria in water, to eliminate the effect of medium components that could block the antibacterial activity. 7 Six exposure times have been investigated: 0, 5, 15, 30, 60 and 90 minutes.…”
Section: Resultsmentioning
confidence: 99%
“…These results are in contradiction to findings by Liu et al (2012) that antibacterial activity of GO sheets against E. coli increased in a size-dependent manner ranging from 0.753 to 0.01 μm 2 . Similarly, Campos-Delgado et al (2016) reported that GO sheets with larger lateral size (> 2 μm) showed higher antibacterial activity against E. coli compared with GO sheets with smaller lateral size (100 nm). The authors suggested that GO wraps the bacterial cells and prevents them from being able to uptake nutrients and proliferate on agar plate leading to reduced counts.…”
Section: Resultsmentioning
confidence: 87%
“…In another report, peripheral blood mononuclear cells were treated with GO nanomaterials, which possessed different dimensions and were dispersed in different aqueous solutions, i.e., GO with dimensions of about 100 nm and more than 2 lm dispersed in water as well as GO with a dimension of roughly 100 nm dispersed in phosphate-buffered saline. 59 It was reported that after 24 h, no adverse biological effect was detected on these GOtreated blood cells.…”
Section: Interactions Of Graphene Nanomaterials With Peripheral Bmentioning
confidence: 99%